Rapid Ability Adaptation of Callosobruchus maculatus to a Novel Host Vigna unguiculata - Soumaya Haouel-Hamdi; Meriem Labidi; Mariam Hedjal-Chebheb; Ali Aouji; Emna Boushih; Jouda Mediouni-Ben Jemâa (Tunisian Journal of Plant Protection, 2018)

(untitled)
In Tunisia, the cowpea seed beetle Callosobruchus maculatus is the major and economic insect pest of stored chickpea. This work aims to study the adaptive behavior of Tunisian strain of C. maculatus exclusively reared on chickpea for 5 years on a novel host, the cowpea Vigna unguiculata. The relative aspects of the host adaptation tests consist of the assessment of the reproductive parameters and the demographic traits of the insect over six months of storage period on chickpea and cowpea seeds. Two types of bioassays free-choice and no-choice were performed. Comparison of reproductive and demographic parameters for C. maculatus showed that under no-choice situation, chickpea was the preferred host of C. maculatus along the first two months of storage. However, under free-choice, the results revealed that from the first month of storage, the reproductive and demographic parameters of C. maculatus shifted in favor of cowpea. Thus, through this work, we have demonstrated the rapid adaptive potential of C. maculatus toward its original host and its ability to recognize and adapt to it over a short period.